EFFЕCIIVENESS OF USING NEW METHODS AND METHODS OF LEARNING THE UKRAINIAN LANGUAGE AS A FOREIGN IN MEDICAL UNIVERSITY - Lychuk, S. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article attempts to identify effective methods of teaching Ukrainian as a foreign language and to base them on the European experience. The most commonly used methods in the European practice of foreign language teaching are characterized: communicative, project, audio-lingual, distance, intensive and blended learning. The advantages of the blended learning system are examined. An interpretation of the term "blended learning" is proposed. The features of the organization of online learning and the structure of blended learning are described. The data of the conducted survey are presented: a) teachers conducting classes in Ukrainian as a foreign language; b) foreign students from different countries. Questionnaire was developed for the survey. The article proposes some tasks for teachers of Ukrainian as a foreign language, commenting on the specifics of different models of blended learning. Based on the results of the survey, the respondents outlined effective methods of teaching a foreign language, identified factors that influence the use of the blended learning model of future doctors when teaching Ukrainian as a foreign language. The advantages and prospects of using blended learning in the educational process of a higher medical institution are analyzed. The results of the study strongly suggest that the blended learning model opens up new possibilities for presenting educational material in a new and accessible form for students.